2008
DOI: 10.1007/s00066-008-1816-4
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class II Alleles and the Presence of Circulating Epstein-Barr Virus DNA in Greek Patients with Nasopharyngeal Carcinoma

Abstract: Circulating EBV-DNA and specific HLA class II alleles may predispose to or protect from NPC. However, the results of this study suggest that the genetic predisposition of an individual to NPC is independent of the liability to EBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
2
0
4
Order By: Relevance
“…Utilizing various genomic approaches, we previously demonstrated the contribution of multiple loci including 6p21, TERT, and MST1R in NPC [5][6][7] . Numerous NPC genetic susceptibility association studies identified the 6p21.3 human leukocyte antigen (HLA) locus 4,7,8,[10][11][12][13][14][15][16][17][18][19][20] , supporting the hypothesis that HLA alleles or nearby non-HLA genes are major genetic determinants for NPC pathogenesis. However, most of these studies were limited by a small sample size 4,8,[11][12][13][14][15][16][17][18][19][20] .…”
mentioning
confidence: 97%
“…Utilizing various genomic approaches, we previously demonstrated the contribution of multiple loci including 6p21, TERT, and MST1R in NPC [5][6][7] . Numerous NPC genetic susceptibility association studies identified the 6p21.3 human leukocyte antigen (HLA) locus 4,7,8,[10][11][12][13][14][15][16][17][18][19][20] , supporting the hypothesis that HLA alleles or nearby non-HLA genes are major genetic determinants for NPC pathogenesis. However, most of these studies were limited by a small sample size 4,8,[11][12][13][14][15][16][17][18][19][20] .…”
mentioning
confidence: 97%
“…В литературе имеются единичные работы, посвященные исследованию распределения частот этого гена у пациентов с РНГ. Опубликована работа, в которой авторы отмечают снижение частоты аллелей DQA1*0103 и DQA1*0201 у пациентов с РНГ греческого происхождения [21]. У представителей народности хань из Китая с диагностированным РНГ было выявлено снижение частоты аллеля DQA1*0201 и увеличение частоты аллеля DQA1*0101 [22].…”
Section: Discussionunclassified
“…При исследовании популяции хань из Китая не удалось обнаружить изменений в распределении гена DQB1 у пациентов с РНГ по сравнению с контрольной группой [13,22]. Также не найдено подобных различий и в греческой популяции [21]. Единственная работа, в которой упоминается связь чувствительности к РНГ и гена DQB1, -это исследование, выполненное в Тунисе, в котором с чувствительностью к РНГ был ассоциирован DQB1*02, а с устойчивостью к этому заболеванию -DQB1*05 [23].…”
Section: Discussionunclassified
See 2 more Smart Citations